Microphysics on winter enhancement of Antarctic stratospheric aerosol: Hydration of sulfuric acid droplets (abstract) - Iwasaka, Yasunobu; Morita, Yasuhiro; Ito, Tomoyuki (1986)
P(論文) departmental bulletin paper